Influence of Incorporating Fluoroapatite Nanobioceramic on the Compressive Strength and Bioactivity of Glass Ionomer Cement - Khaghani M; Alizadeh S; Doostmohammadi A (Shiraz University of Medical Sciences, 2016)
Statement of Problem: In order to increase the performance of glass ionomer cement, it is reinforced with metal powders, short fibers, bioceramics and other materials. Fluoroapatite(Ca10(PO4)6F2) is found in dental enamel and is usually used in dental materials due to its good chemical and physical properties. Objectives: In this study, the effects of the addition of synthesized fluoroapatite nanoceramic on the compressive strength and bioactivity of glass ionomer cement were investigated. Materials and Methods: The synthesized fluoroapatite nanoceramic particles (~ 70 nm) were incorporated into as-prepared glass ionomer powder and were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Moreover, the compressive strength values of the modified glass ionomer cements with 0, 1, 3 and 5 wt% of fluoroapatite were evaluated. Results: Results showed that glass ionomer cement containing 3 wt%fluoroapatite nanoparticles exhibited the highest compressive strength (102.6± 4) compared to the other groups, including control group. Furthermore, FTIR and SEM investigations indicated that after soaking the glass ionomer cement- 3 wt% fluoroapatite composite in the simulated body fluid solution, the intensity of O-H, P-O and C-O absorption bands increased as a result of the formation of apatite layer on the surface of the sample, and the rather flat and homogeneous surface of the cement became more porous and inhomogeneous. Conclusions: Addition of synthesized nano-fluoroapatite to as-prepared glass ionomer cement enhanced the compressive strength as well as nucleation of the calcium phosphate layer on the surface of the composite. This makes it a good candidate for dentistry and orthopedic applications.